Validity of notary deed based on incorrect documentation data - David Hardjo,; Slamet Suhartono,; Endang Prasetyawati,; Otto Yudianto, (Technium Social Sciences Journal, 2021)
This type of research is normative legal research. Notary deed made based on incorrect document data, doesn’t cause the deed to be degraded in its validity. This means that the deed is still considered valid. However, the validity depends on the authenticity of the deed in question, namely whether the deed was made in accordance with the law, in this case the 2014 Notary Law carried out in accordance with the correct procedure, and there are no elements of substance defects in its manufacture for other purposes. Contradiction of the validity of the deed which was made based on incorrect document data, of course, is not necessarily justified.